Application of the methane saturated dispersion resonance near 2.36μm over the temperature range of 77–300 K for optical frequency standards. (July 2016) - Tarabrin, Mikhail K.; Lazarev, Vladimir A.; Karasik, Valeriy E.; Kireev, Alexey N.; Korostelin, Yuri V.; Shelkovnikov, Alexander S.; Tuyrikov, Dmitry A.; Kozlovsky, Vladimir I.; Podmar'kov, Yuri P.; Frolov, Mikhail P.; Gubin, Mikhail A.
Abstract: New spectroscopic knowledge of the ν 1 + ν 4 R(2) E line of methane over the temperature range 77–300 K is reported. Theoretical calculations of the absorption coefficient and the amplitudes of saturated dispersion resonances at 4234 cm −1 were derived. The theoretical dependence on the temperature of the amplitudes of the saturated dispersion resonances was obtained. A novel setup based on a Cr 2 + : ZnSe laser was used for Doppler-free spectroscopy of methane. The amplitudes of the saturated dispersion resonances of the ν 1 + ν 4 R(2) E line of methane were measured experimentally at different temperatures. A comparison with theoretical dependence supports the reliability of the experiment. The obtained results are of immediate interest in applications demanding laser frequency stabilization.